Monocyte, Lymphocyte, and Monocyte–Lymphocyte Ratio Responses to Treatment Phases in Pulmonary Tuberculosis Patients - Nurul Hidayathul Mahpudinah Restu; Leka Lutpiatina; Ahmad Muhlisin; Ratih Dewi Dwiyanti (Baiman Bauntung Batuah Center, 2026)
Pulmonary tuberculosis is a chronic infectious disease that affects the balance of innate and adaptive immune responses, reflected in changes in hematological parameters, particularly monocyte and lymphocyte counts, and the monocyte-lymphocyte ratio (MLR). This study aimed to analyze differences in lymphocyte and monocyte counts and MLR values ??in pulmonary tuberculosis patients based on treatment phase. This cross-sectional analytical survey study involved 60 pulmonary tuberculosis patients divided into 0-month treatment groups, the intensive phase, and the continuation phase in Loa Kulu District from January to April 2025. Peripheral blood smears were stained with Giemsa to determine the percentage of lymphocytes and monocytes, and then the MLR value was calculated. Statistical analysis using one-way ANOVA showed significant differences in lymphocyte and monocyte counts between treatment groups (p<0.05). The mean lymphocyte count increased with treatment duration, while the mean monocyte count decreased, resulting in a decrease in the MLR value from 0.64 in the pre-treatment group to 0.29 in the intensive phase and 0.22 in the continuation phase. The decrease in MLR reflects an improved immune response balance and decreased systemic inflammation during tuberculosis therapy. The results of this study indicate that MLR demonstrated variation across treatment phases, suggesting its potential relevance in the clinical assessment of TB patients.